EFFECT OF COMPENSATION AND BENEFIT TO EMPLOYEE ENGAGEMENT THROUGH ORGANISATION BRAND IN INDONESIA’S STARTUP COMPANY - Astri Utami Indriyani; Heruwasto Ignatius (Program Studi Magister Manajemen FE Unsri, 2016)
Startup business in Indonesia has become a popular way to start the business. Startup is as well a promised business in thefiled og investation and pay/salary. Does pay and facility is suit well with their job description and makes the engage to company? This paper tests the hypothesis that compensation and benefit have effect on employee engagement with organisation brand in between. Result shows that organisation brand failed to be mediating variable just because only compensation who have effect, that is on organisation brand and employee engagement. Which engagement is affected as well by compensation